The Effects of A Cognitive-Behavioral Therapy Program in Conjunction with Social Support on the Social Functioning and Mental Health of Patients with Comorbid Amphetamine Dependence and Psychotic Disorders in a Treatment Center in Pathumthani Province. - Wingworn, Sasiporn; Takviriyanun, Nidtaya; Jirarode, Angkana (Journal of The Royal Thai Army Nurses, 2023)
This quasi-experimental study aimed to determine the effectiveness of a cognitive-behavioral therapy program in conjunction with social support on the social functioning and mental health of patients with comorbid amphetamine dependence and psychotic disorders. The seventy-five samples had comorbid amphetamine dependence and psychotic disorders undergoing rehabilitation at a treatment center in Pathum Thani Province, Thailand. The samples were randomized evenly into experimental and control groups. Thirty-eight samples in the experimental group received eleven sessions of the cognitive and behavioral therapy program in conjunction with social support and standard care. The thirty-seven samples in the control group received standard care. Data were collected before and a week after the trial, using questionnaires that evaluated the patients’ social function and mental health (DASS-21). Personal information forms were used to collect the data. The participant’s social functioning and mental health status scores were measured using questionnaires that evaluated the patients’ social function and mental health (DASS-21) before and after the cognitive and behavioral therapy program in conjunction with social support. Descriptive statistics were used to represent the personal information about the participants; a dependent t-test was used to compare the mean of the social functioning and mental health status scores before and after the intervention in each group; and MANOVA was used to examine the mean differences social functioning and mental health status scores between the experimental and control groups. The results showed that after the trial, the mean scores for the social functioning of the experimental group were statistically higher than before the trial and for those of the control group (p<.001). Additionally, the mean scores for mental health related to the depression, anxiety, and stress of the experimental group were significantly lower than before the trial and for those of the control group (p< .001).